2013
DOI: 10.1016/j.molimm.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the dimer formation of Fcα/μ receptor (CD351)

Abstract: Fcα/μR (CD351) is an Fc receptor for both IgA and IgM and forms an atypical dimer that is resistant to reduction by 2-mercaptoethanol or boiling. We previously demonstrated that the cytoplasmic portion of Fcα/μR is required for dimer formation and for its efficient cell-surface expression. However, the biochemical nature of these phenomena has not been determined. By using a BW5147 mouse cell line expressing deletion mutants of the cytoplasmic region of Fcα/μR, we found that the region spanning amino acids 504… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Feamr gene is located near the clusters for IgG FcRs on chromosome 1 (refs 15 , 17 , 18 ). The cytoplasmic region of Fcα/μR is required for an atypical dimer formation 19 20 . Fcα/μR is preferentially expressed on follicular dendritic cells in the lymphoid organs 21 and suppresses T -independent antigen retention by follicular dendritic cells, leading to the downregulation of germinal centre formation and humoral immune responses, including antibody production, affinity maturation and memory B-cell generation, against T -independent antigens 21 .…”
mentioning
confidence: 99%
“…Feamr gene is located near the clusters for IgG FcRs on chromosome 1 (refs 15 , 17 , 18 ). The cytoplasmic region of Fcα/μR is required for an atypical dimer formation 19 20 . Fcα/μR is preferentially expressed on follicular dendritic cells in the lymphoid organs 21 and suppresses T -independent antigen retention by follicular dendritic cells, leading to the downregulation of germinal centre formation and humoral immune responses, including antibody production, affinity maturation and memory B-cell generation, against T -independent antigens 21 .…”
mentioning
confidence: 99%
“…Surprisingly, immunoblotting analyses of transfectants simultaneously expressing two types of Fcα/μR tagged with Flag and HA (hemagglutinin) at the N‐terminus demonstrated that Flag‐tagged Fcα/μR was not coimmunoprecipitated with HA‐tagged Fcα/μR. Conversely, an anti‐HA antibody immunoprecipitated HA‐tagged Fcα/μR alone, but not Flag‐tagged Fcα/μR . These results suggest that Fcα/μR does not form homodimers.…”
Section: Molecular Characteristics Of Fcα/μrmentioning
confidence: 94%
“…In contrast to BW5147 transfectants expressing WT Fcα/μR, which shows both monomeric and dimeric formations, BW5147 cells transfected with mutated Fcamr cDNA encoding Fcα/μR lacking the cytoplasmic portion expressed only monomeric Fcα/μR protein , suggesting that the cytoplasmic portion is required for dimer formation of Fcα/μR and efficient cell surface expression of Fcα/μR. Further analyses demonstrated that the regions spanning 481–490 and 504–523 amino acids are essential for dimer formation and efficient cell surface expression of Fcα/μR, respectively ( Fig. ).…”
Section: Molecular Characteristics Of Fcα/μrmentioning
confidence: 95%
“…FcR forms an atypical dimer, for which the cytoplasmic region of FcR is required (Cho et al, 2010;Takagaki et al, 2013). FcR is moderately expressed on B cells and macrophages (Sakamoto et al, 2001;Shibuya et al, 2000), and most strongly on follicular dendritic cells (FDCs) (Cho et al, 2006;Honda et al, 2009;Usui et al, 2012), which is involved in germinal center (GC) formation (Chaplin and Zindl, 2006;Park and Choi, 2005).…”
Section: Introductionmentioning
confidence: 99%